Volatile trace metals deposited in ice as soluble volcanic aerosols during the 17.7.ka eruptions of Mt Takahe, West Antarctic Rift - Mason, Emily; Edmonds, Marie; McConnell, Joseph R. (Frontiers in Earth Science, 2022)
Volatile metals are emitted at significant rates as gases and particulates from volcanoes, although their speciation, bioreactivity and longevity during atmospheric transport are essentially unknown. Ice cores provide detailed yet largely unexplored long-term records of volcanogenic volatile metals in air and precipitation. Here we evaluate the source and speciation of volatile metals (cadmium, lead, bismuth, and thallium) in Antarctic ice cores from the massive, halogen-rich and sulfur-poor ~17.7 ka eruptions of Mt. Takahe, West Antarctic Rift. We show that these volatile, chalcophile metals were transported to the ice core as soluble aerosol, derived from magma degassing, in contrast to lithophile elements in the ice core that were transported as silicate ash. We use correlation analysis and chemical speciation modelling of the chlorine-rich volcanic plume to show that the volcanic metals cadmium, lead and bismuth were likely transported as water-soluble chloride aerosols in the atmosphere before they were scavenged from the plume by ice, water or ash and deposited onto the ice within 400 km of the vent. Our findings show that as well as recording trace metals sourced from much more distal regions, ice cores from Antarctica also record clear signatures of regional continental volcanism in the form of chloride aerosol.